PROSPECTS AND TRENDS OF DIGITAL TWINS IN EDUCATION (Uzbek Scholar Journal, 2023)
This article briefly describes the nature, problems and issues of digitization of education, the perspective of the "digital twin" of the learner for the development of person-oriented education as an important issue of the process of digital transformation in education in the age of digital technologies, and the tendency of its development is mentioned.